Perbedaan Efektivitas Ekstrak Ikan Gabus Dan Daun Binahong Terhadap Lama Penyembuhan Luka Operasi Sectio Caesarea Pada Ibu Nifas - Intan Nugraheni; Ari Kurniarum (Poltekkes Kemenkes Surakarta, 2016)
Abstract: Mother Parturition, Sectio Caesarea, Wound Healing. To identify differences in the effectiveness of extracts of catfish and leaves binahong towards healing old wounds sectio Caesarea operation on postpartum mothers. There is a difference in the effectiveness of extracts of catfish and leaves binahong towards healing old wounds sectio Caesarea operation on postpartum mothers. The study design was a Quasi Experimental research design with a pretest-posttest nonequivalent control group. The sampling technique was an accidental sampling technique. The number of samples 60 puerperal women with puerperal women inclusion criteria prime and multiparous, type transverse incision, wound care treatment and the same. Statistical analysis using the Wilcoxon test with significant value in the study was p<0.05. The average length of the wound healing process operation sectio Caesarea in postpartum mothers who consume fish extract the cork is 8 days, binahong leaf extract is 12 days whereas the control group without treatment was 16 days. There are differences in the effectiveness of extracts of catfish and leaves binahong towards healing old wounds sectio Caesarea operation in puerperal women with p-value 0.013. There are differences in the effectiveness of extracts of catfish and leaves binahong towards healing old wounds sectio Caesarea operation at BPM puerperal women in the District of Tulung with p = 0.013 (p <0.05).